The Influence of Digital and Technology Equipment in Learning Activities on Students' Written Skills - Muhammadiah, Mas'ud; Wariunsora, Marlen; Ridhwan, Muhammad; Sjeny Liza Souisa; Denissa Alfiany Luhulima (Jurnal Informasi dan Teknologi, 2024)
This research aims to observe how students develop their written narrative skills. This research uses survey instruments and questionnaires as data collection methods. Statistical methods are used in data analysis. One hundred students were involved in this research, except those who only wrote less than seven texts from the research sample. The study results show that students experience significant development in their linguistic expression in written communication situations. Their ability to produce texts becomes richer at the linguistic level, with increased lexical diversity in nominal and verbal areas. They also showed a better ability to use sentence-connecting devices. However, there are differences between students who use their mother tongue and those who use their second language in terms of lexis and syntax. Students who use their mother tongue tend to use less and less varied lexis than their second language. In addition, students also showed higher linguistic uncertainty, especially in terms of case inflection and syntax. Nevertheless, there are no significant differences between the two language groups regarding the global structure of the texts. The results of this study provide important insights for language education at the primary school level, showing that students who use their mother tongue have sufficient ability to carry out narrative tasks in a manner comparable to students who use a second language of the same age. However, it should be noted that the development of language skills in students who use their mother tongue may take longer and require special attention in language learning.